Digital Marketing's Impact on Consumer Choices: Dampak Pemasaran Digital terhadap Pilihan Konsumen - Indayani, Lilik; Maulidiyah, Nur Laili (Universitas Muhammadiyah Sidoarjo, 2024)
In the digital era, internet advancements have significantly enhanced efficiency in the tea beverage business. This study investigates the impact of digital marketing strategies, product innovation, and brand awareness on consumer purchasing decisions for Indonesian Iced Tea products. Using a quantitative approach and data from 96 respondents selected via the Lemeshow formula, multiple linear regression analysis revealed that all three variables significantly influence purchasing decisions. These findings highlight the critical role of digital marketing, innovation, and brand awareness in driving consumer choices, offering valuable insights for marketers to enhance their strategies. Highlight: Digital marketing significantly boosts consumer purchasing decisions. Product innovation is essential for market competitiveness. Strong brand awareness influences consumer choices. Keyword: Digital marketing, product innovation, brand awareness, consumer purchasing decisions, Indonesian Iced Tea